Gastric Adenocarcinoma of Fundic Gland Type Treated by Endoscopic Submucosal Dissection - Yong Bo Park; Gwang Ha Kim; Kyungbin Kim; Tae Kyoung Ha; Guk Bin Park; Young Min Kwak (Yong Chan Lee, 2021)
Gastric adenocarcinoma of fundic gland type is known to originate from the gastric mucosa of the fundic gland region without intestinal metaplasia. It is difficult to detect during endoscopy and diagnose histopathologically. The development of immunohistochemistry has enabled the diagnosis of gastric adenocarcinoma of fundic gland type by gastric phenotype. A 34-year-old man visited us for treatment of a 5 cm-sized low-grade dysplasia in the gastric fundus which was incidentally found during a health check-up endoscopy. Endoscopic submucosal dissection was performed successfully, and the final histopathology showed gastric adenocarcinoma of fundic gland type. Herein, we report a rare case of gastric adenocarcinoma of fundic gland type and its endoscopic and histopathologic findings.